Regulation mechanism of endoplasmic reticulum stress on metabolic enzymes in liver diseases - Shaojun Zhou; Kaiwen Cheng; Yi Peng; Yuxi Liu; Qingqing Hu; Su Zeng; Xuchen Qi; Lushan Yu (Elsevier, 2024)
The endoplasmic reticulum (ER) plays a pivotal role in protein folding and secretion, Ca2+ storage, and lipid synthesis in eukaryotic cells. When the burden of protein synthesis and folding required to be handled exceeds the processing capacity of the ER, the accumulation of misfolded/unfolded proteins triggers ER stress. In response to short-term ER stress, the unfolded protein response (UPR) is activated to allow cells to survive. When ER stress is severe and sustained, it typically provokes cell death through multiple approaches. It is well documented that ER stress and metabolic deregulation are functionally intertwined, both are considered contributing factors to the pathogenesis of liver diseases, including non-alcoholic fatty liver disease (NAFLD), alcoholic liver disease (ALD), ischemia/reperfusion (I/R) injury, viral hepatitis, liver fibrosis, and hepatocellular carcinoma (HCC). Hepatocytes are rich in smooth and rough ER, which harbor metabolic enzymes that are capable of sensing alterations in various nutritional status and external stimuli. Extensive research has focused on the molecular mechanism linking ER stress with metabolic enzymes. The purpose of this review is to summarize the current knowledge regarding the effects of ER stress on metabolic enzymes in various liver diseases and to provide potential therapeutic strategies for chronic liver diseases via targeting UPR.